2022
DOI: 10.1016/j.surg.2021.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and impact of postoperative pancreatic fistula after minimally invasive and open distal pancreatectomy

Abstract: Background: Previous studies reported a higher rate of postoperative pancreatic fistula after minimally invasive distal pancreatectomy compared to open distal pancreatectomy. It is unknown whether the clinical impact of postoperative pancreatic fistula after minimally invasive distal pancreatectomy is comparable with that after open distal pancreatectomy. We aimed to compare not only the incidence of postoperative pancreatic fistula, but more importantly, also its clinical impact. Methods: This is a post hoc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This suggests that the impact of the increased risk of POPF in MIDP is small. Previous studies have indeed suggested that POPF after MIDP is associated with less additional radiological drainage and shorter length of drainage 38 . The increased rate of interventions over time in the present study (7.9% to 17.8%) is probably related to the implementation of the algorithm used in the PORSCH trial since 2018, 39 which lowered the threshold for radiological drainage but also lead to a decrease in ICU admissions after MIDP over time (12.4% to 4.6%), which demonstrates that timely recognition of complications such as POPF may improve patient outcome.…”
Section: Discussionmentioning
confidence: 89%
“…This suggests that the impact of the increased risk of POPF in MIDP is small. Previous studies have indeed suggested that POPF after MIDP is associated with less additional radiological drainage and shorter length of drainage 38 . The increased rate of interventions over time in the present study (7.9% to 17.8%) is probably related to the implementation of the algorithm used in the PORSCH trial since 2018, 39 which lowered the threshold for radiological drainage but also lead to a decrease in ICU admissions after MIDP over time (12.4% to 4.6%), which demonstrates that timely recognition of complications such as POPF may improve patient outcome.…”
Section: Discussionmentioning
confidence: 89%
“…The risk of POPF is the major impacting complication after open and laparoscopic DP and is highly related to prolonged intra-abdominal drainage, hemorrhage, readmissions, sepsis and certainly mortality[ 87 , 88 ]. Older studies reported a higher rate (39%) of POPF after minimally invasive DP compared to open DP[ 89 ], but others failed to find significant differences after careful statistical patient stratification and homogenization[ 90 ]. Moreover, in 2021, a new POPF risk score (ua-FRS) was validated for minimally invasive pancreatic surgery[ 91 ], with a reported global incidence rate of 21%.…”
Section: Laparoscopic Dpmentioning
confidence: 99%
“…Postoperative pancreatic fistula (POPF) is a severe complication caused by pancreatoenteric anastomotic leakage, that occurs in about 10-30% of patients undergoing pancreatic head resection for surgical treatment of pancreatic cancer [112][113][114][115][116][117][118].…”
Section: Post-operative Pancreatic Fistulamentioning
confidence: 99%